Antioxidant Activity of Urtica dioica: An Important Property Contributing to Multiple Biological Activities - Varun Jaiswal; Hae-Jeung Lee (MDPI AG, 2022)
Urtica dioica (UD) is a multi-functional plant known to be used as both food and medicine from ancient times. The plant has the potential to be used as a fertilizer and for biological pest control. It is also used in textile and related industries for its quality fibers. In the recent past, the plant has received great attention for its numerous important biological activities and food applications. The antioxidant activity of UD is the crucial factor supporting its important biological activities, such as anticancer, antidiabetic and anti-inflammatory properties. The antioxidant activity of UD is also found to be protective in different organs, including the brain, liver, lungs, kidney, ovary, and uterus, and may also be protective against diseases associated with these organs. Few clinical studies have endorsed the antioxidant potential of UD in patients. The current work is an attempt to comprehensively compile and discuss the antioxidant activity of UD from in vitro, in vivo and human studies. The insights of the current study would be helpful in getting a panoramic view of the antioxidant potential of UD, and provide direction for optimizing and developing it for therapeutic applications against important diseases and conditions in the near future.